If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -3(2 + -1x) = 5x 4 + (2 * -3 + -1x * -3) = 5x 4 + (-6 + 3x) = 5x Combine like terms: 4 + -6 = -2 -2 + 3x = 5x Solving -2 + 3x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -2 + 3x + -5x = 5x + -5x Combine like terms: 3x + -5x = -2x -2 + -2x = 5x + -5x Combine like terms: 5x + -5x = 0 -2 + -2x = 0 Add '2' to each side of the equation. -2 + 2 + -2x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -2x = 0 + 2 -2x = 0 + 2 Combine like terms: 0 + 2 = 2 -2x = 2 Divide each side by '-2'. x = -1 Simplifying x = -1
| 11x+17-6x=2 | | (x^2+4x-16i-4xi)=0 | | 7/5*y=14/5 | | 5-7x+3=-3x-11+15x | | 12=10x+4x-16 | | 4/24=16/x | | 60/5=6/x | | 60/5=10/x | | x=1/2y-5 | | 12-4x=10x-16 | | 55/11=5/x | | 50/5=10/x | | 2/5*x=28 | | 7x+14=-15x-6 | | 0.30=log(x) | | 42/7=14/x | | 21x-6-18x+2=17x-8-14x+11 | | 42/7=6/x | | 7/42=6/x | | 3x^9u^2*7u^6*2x= | | 27x^2+3x-10=0 | | 2v^9x^2*3x^7*7v= | | 2.1+3b=1.8 | | 12/24=6/x | | y+50=x | | 16x^2+65.5x+5.5=0 | | 9x-6=8x+11 | | 5p-0.48=0.12 | | 2y-1=5y-10 | | 3/4x4/9 | | h=6+17t-16t+2 | | 7w*2w^8v^4*3v^2= |